Diffuse panbronchiolitis as a rare complication of thymectomy and radiation therapy in a patient with thymoma: a case report - Lu, Ye; Qi, Qi; Qu, Dan; Chen, Yu (Frontiers in Oncology, 2025)
BackgroundDiffuse panbronchiolitis (DPB) is an uncommon respiratory disorder characterized by the presence of respiratory bronchiolitis and persistent inflammation in adjacent tissues, which can be effectively treated with early diagnosis and intervention. DPB is a rare complication associated with thymoma that remains poorly understood, especially when it occurs in conjunction with acquired cellular immune deficiency.Case presentationWe present a case of DPB in a patient with thymoma following thymectomy and radiation therapy. A 47-year-old Chinese man underwent thymectomy due to the presence of a mediastinal mass, and pathological examination confirmed a type B2 thymoma. He also underwent 25 sessions of radiation therapy. The patient’s respiratory symptoms, including cough, expectoration, and shortness of breath, worsened significantly after radiation treatment. Immune dysfunction, marked by CD4+ T cell immunodeficiency with normal immunoglobulin levels, was observed. Chest computed tomography revealed diffuse nodules with tree-in-bud signs and new consolidation within the irradiated area, leading to a diagnosis of combined DPB and radiation pneumonitis. The patient’s symptoms and lung imaging findings significantly improved after the initiation of low-dose oral azithromycin for DPB and low-dose glucocorticoid therapy for radiation pneumonitis.ConclusionsClinicians should consider DPB in patients with thymoma and cellular immunodeficiency. Both thymectomy and radiation therapy can contribute to the development of DPB. Early treatment with macrolides can improve patient prognosis.